iPS Cell-Based Model for MAPT Haplotype as a Risk Factor for Human Tauopathies Identifies No Major Differences in TAU Expression - Strauß, Tabea; Marvian-Tayaranian, Amir; Sadikoglou, Eldem; Dhingra, Ashutosh; Wegner, Florian; Trümbach, Dietrich; Wurst, Wolfgang; Heutink, Peter; Schwarz, Sigrid C.; Höglinger, Günter U. (Frontiers in Cell and Developmental Biology, 2021)
The H1 haplotype of the microtubule associated protein tau (MAPT) gene is a common genetic risk factor for some neurodegenerative diseases such as progressive supranuclear palsy, corticobasal degeneration, and Parkinson’s disease. The molecular mechanism causing the increased risk for the named diseases, however, remains unclear. In this paper, we present a valuable tool of eight small molecule neural precursor cell lines (smNPC) homozygous for the MAPT haplotypes (four H1/H1 and four H2/H2 cell lines), which can be used to identify MAPT-dependent phenotypes. The employed differentiation protocol is fast due to overexpression of NEUROGENIN-2 and therefore suitable for high-throughput approaches. A basic characterization of all human cell lines was performed, and their TAU and α SYNUCLEIN profiles were compared during a differentiation time of 30 days. We could identify higher levels of conformationally altered TAU in cell lines carrying the H2 haplotype. Additionally, we found increased expression levels of α SYNUCLEIN in H1/H1 cells. With this resource, we aim to fill a gap in neurodegenerative disease modeling with induced pluripotent stem cells (iPSC) for sporadic tauopathies.